Sources of acetic and other fatty acids and their role in sluggish and stuck red wine fermentations - Du Toit, Wessel J. (Wessel Johannes) (Stellenbosch : Stellenbosch University, 2012)
Thesis (MScAgric)--University of Stellenbosch, 2000.